Bacteriocin: A natural approach for food safety and food security - Lahiri, Dibyajit; Nag, Moupriya; Dutta, Bandita; Sarkar, Tanmay; Pati, Siddhartha; Basu, Debarati; Abdul Kari, Zulhisyam; Wei, Lee Seong; Smaoui, Slim; Wen Goh, Khang; Ray, Rina Rani (Frontiers in Bioengineering and Biotechnology, 2022)
Screech to cater for the hungry is a worldwide menace in the 21st century. The food security is the utter most prime factor for the increasing demand for food. Along with food safety, biopatenting for the people belonging to the poor communities should be pivoted by this time. From the last few years awareness for human health about using chemical preservatives in food has increased. Novel preservatives along with novel preservation methods have been instigated due to intensified demand of extended shelf-life along with prevention of food spoilage of the dairy products. Bacteriocins are the antimicrobial peptides which are considered as safe due to its tranquil degradation at the mammalian gastrointestinal tract by proteolytic enzymes. Bacteriocins are usually produced by the lactic acid bacteria (LAB), a group of Gram positive bacteria that occurs naturally in foods and has safe records in the dairy industry. Bacillus spp. are another group of bacteriocin producing Gram positive bacteria which have potential to reduce food spoilage by controlling pathogenic bacterial growth. Bacteriocins are thermostable, pH tolerant proteolytically active in nature which make its usage convenient to the food industry. Several researches are going on in the domain of bio-preservation which can be implemented in food safety and food security.